Physical fitness of students of universities of the Siberian region in comparative context with the standards of the all-russian physical skills GTO - Kadomtseva, E.M.; Ponomarev, V.V.; Fateeva, T.V.; Grigoriev, V.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study The aim of the study is to conduct a theoretical and statistical analysis of the physical fitness of students in the Siberian region, comparing it with the standards of the GTO Physical Fitness Test (Level VII), to identify trends and to develop corrective scientific and methodological measures. Methods and structure of the study. The study was conducted between 2024 and 2025. First- and second-year students took part in the study from: Siberian Federal University, Krasnoyarsk (SFU); Krasnoyarsk State Medical University named after Prof. V.F. Voino-Yasenetsky, Ministry of Health of Russia (KSMU); Siberian State University of Science and Technology named after Academician M.F. Reshetnev, Krasnoyarsk (SSUST); and Krasnoyarsk State Agrarian University (KSAU). The total sample size was 1,450 students. Over a two-year period, follow-up testing of physical fitness indicators was conducted among male and female students: 100 m run (male and female students), 3000 m run (male students), 2000 m run (females) sit-ups in one minute (females) and pull-ups on a high bar (males). The results of the fitness tests yielded over 4,500 physical fitness indicators. This statistical data was analysed using mathematical statistics and compiled into tables. Furthermore, an analysis of the physical fitness indicators was carried out against the standards of the GTO Physical Culture and Sports System – Level VII, on the basis of which the main conclusions were formulated. Results and conclusions. The analytical study revealed a low level of physical fitness among university students in the Krasnoyarsk Krai, whose results do not meet the GTO standards. Female students’ physical fitness indicators are higher than those of male students; in the 100-metre sprint, their results correspond to the GTO bronze badge, and in the one-minute sit-up test, to the silver badge. At the same time, for male students, the GTO bronze badge is achieved only in the 100-metre sprint. To address the aforementioned identified issues in the physical education of university students, the following innovative organisational and methodological measures are proposed to improve the content and focus of the current physical education system for students: to restructure the targeted content of the physical education curriculum for students at the university, specifically to prepare them to meet the GTO physical fitness standards; to design a sport-specific approach to physical education that enables students to develop the skills and abilities required for selected sports (Specialist Diploma + competitive athlete); to implement a comprehensive approach to students’ physical education aimed at encouraging students to engage actively in physical education and sport and at improving the physical fitness of future specialists.